2022
DOI: 10.1111/myc.13442
|View full text |Cite
|
Sign up to set email alerts
|

Eumycetoma causative agents are inhibited in vitro by luliconazole, lanoconazole and ravuconazole

Abstract: Introduction Eumycetoma is a subcutaneous mutilating disease that can be caused by many different fungi. Current treatment consists of prolonged itraconazole administration in combination with surgery. In many centres, due to their slow growth rate, the treatment for eumycetoma is often started before the causative agent is identified. This harbours the risk that the causative fungus is not susceptible to the given empirical therapy. In the open‐source drug program MycetOS, ravuconazole and luliconazole were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…In the current study, three antifungals comprising luliconazole, lanoconazole and efinaconazole demonstrated the highest antifungal activity among all tested. Several previous studies have shown that luliconazole and lanoconazole have excellent antifungal activity against the most clinically important fungi including Aspergillus , Candida , Malassezia and melanised fungi 29–33 . Among the triazoles tested in our study, efinaconazole had significantly higher activity than the others.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…In the current study, three antifungals comprising luliconazole, lanoconazole and efinaconazole demonstrated the highest antifungal activity among all tested. Several previous studies have shown that luliconazole and lanoconazole have excellent antifungal activity against the most clinically important fungi including Aspergillus , Candida , Malassezia and melanised fungi 29–33 . Among the triazoles tested in our study, efinaconazole had significantly higher activity than the others.…”
Section: Discussioncontrasting
confidence: 45%
“…Several previous studies have shown that luliconazole and lanoconazole have excellent antifungal activity against the most clinically important fungi including Aspergillus, Candida, Malassezia and melanised fungi. [29][30][31][32][33] Among the triazoles tested in our study, efinaconazole had significantly higher activity than the others. Efinaconazole had a GM MIC of 0.98 μg/ml, which was higher than luliconazole (GM MIC 0.004 μg/ml) and lanoconazole (GM MIC 0.012 μg/ml) but lower than main options for fusariosis such as amphotericin B (1.03 μg/ml), voriconazole (2.03 μg/ml) and posaconazole (4.39 μg/ml).…”
Section: Discussionmentioning
confidence: 60%
“…In its current topical formulation, LLCZ is effective only against superficial skin mycoses ( 17 ). Due to the low solubility of the drug, treatment of a deep-seated infection is challenging because of its retention in the skin ( 29 ). This could mean that the development of a systemic LLCZ treatment will not be straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the unknown mechanism of action, and the unavailability of an oral formulation, LLCZ has also shown a poor solubility and retention in the skin. However, the drug shows no concerning side effects, and oral formulations have yielded good results in murine models during its development phase ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Eumycetoma treatment includes the use of oral antifungal medication (i.e., itraconazole, ketoconazole, lanoconazole, luliconazole, posaconazole, ravuconazole, voriconazole). Nevertheless, more complex and incontrollable cases may require surgery and amputation [ 191 , 192 , 193 ]. Several phytotherapeutic alternatives, such as Acacia nubica , Nigella sativa , Boswellia papyrifera , Melaleuca alternifolia , Moringa oleifera , Zingiber officinalis , Piper nigrum , Eugenia caryophillus , and Cinnamomum verum , have been suggested, with positive effects on the treatment of this disease [ 194 ].…”
Section: Fungal Infectionsmentioning
confidence: 99%